The role of heparan sulfate maturation in cancer: A focus on the 3O-sulfation and the enigmatic 3O-sulfotransferases (HS3STs). (May 2020) - Gulberti, Sandrine; Mao, Xianqing; Bui, Catherine; Fournel-Gigleux, Sylvie
Abstract: Heparansulfate (HS) modifications are master regulators of the cross-talk between cell and matrix and modulate the biological activity of an array of HS binding proteins, including growth factors and chemokines, morphogens and immunity cell receptors. This review will highlight the importance of HS maturation mediated by N-deactetylase/sulfotransferases, 2O- and 6O-sulfotransferases in cancer biology, and will focus on the 3O-sulfotransferases and on the terminal, rare 3O-sulfation, and their important but still enigmatic impact in cancer progression. The review will also discuss the molecular mechanisms of action of these HS modifications with regards to ligand interactions and signaling in the cancer process and their clinical significance.